THE LEGAL STUDY OF INHERITANCE RIGHTS FOR CHILDREN OF SURROGATE MOTHER - Sembiring, Idha Aprilyana; Chairi, Zulfi; Barus, Utary Maharany (Jurnal Pembaharuan Hukum, 2024)
A surrogate mother is an agreement between a woman who binds herself with a biological parents to instill of the fertilization on her womb. When the baby borned, must be handed over. According to Indonesian law, surrogacy is prohibited, it causes problems such as inheritance rights. The aims of the research are to examine the inheritance rights of children of a surrogate mother, with normative juridical research approach to examine research objects based on positive law, examining secondary data sources such as primary legal materials such as laws, secondary legal materials such as journals and results of previous research, tertiary legal materials are dictionaries and encyclopedia. descriptive analytical is used to describing phenomena and identifying patterns and relationships. This research was supported by interviewed competent informants. The qualitative analysis was used by analyzing information that cannot be measured. The results are the child is the heir of the surrogate mother because she gave birth to him viewed from a sharia perspective but from the lineage, the child is the heirs of their biological parents. The Civil Code regulates that inheritance rights will be determined by the status of the child, whether an illegitimate child or a legitimate child.